Sosialisasi Moderasi Beragama dalam menjaga Hubungan Konstruktif Antar Umat Beragama di Muna Barat - Fathun, Laode Muhamad; Nathania, Vania Zahra; Wahidah, Tuhfahtu Hasanatul (Jaanur ElBarik Indonesia, 2025)
This research aims to explain the meanings and strategies for managing interreligious relationship in order to create collective awareness and harmony in multicultural religious communities. The research used an exploratory qualitative method. Data collection techniques are observation, empirical review and interviews. The results obtained are that the community in West Muna is very multicultural. This happened as a result of a government program which made the area a migration area for Balinese, Javanese and Bugis residents. This assimilation makes West Muna multicultural, consisting of multiple religions, tribes and ethnicities. However, what happened there actually created harmony and kinship between religious, ethical and cultural communities. This happens because they have the idea of collective social construction or collective identity. This love creates solidarity and pluralist awareness so that it becomes a cosmopolitan form in West Muna. Empirically, there has never been any social and political conflict in West Muna even though we entered the political year. This cannot be separated from the cultural awareness and cultural identity of the Muna people. This identity becomes a guide for relationships between them and can maintain harmony and harmony